Comparison of Division of Joint Property after Divorce in Indonesia and Malaysia - Afrijal, Afrijal; Kharisma Radhityas, Nuryasinta (Universitas Negeri Gorontalo, 2025)
This study compares the legal and regulatory frameworks for the division of joint property after divorce in Indonesia and Malaysia, and analyzes the social and economic factors that influence the process. In Indonesia, the division of joint property is regulated by Law No. 1 of 1974 on Marriage and Law No. 23 of 2004 on the Elimination of Domestic Violence, which accommodate the diversity of customary law and secular approaches. Meanwhile, in Malaysia, the division of joint property is more influenced by Sharia law integrated with the common law system, providing a more structured and consistent procedure for Muslims. The study also identifies social and economic factors such as gender roles, education level, economic conditions, employment status, cultural norms, and power dynamics in the marital relationship as key determinants of the division of joint property. The results show that although both countries have similar cultures and are predominantly Muslim, differences in the integration of Sharia and secular law as well as socio-economic factors create significant variations in the implementation of the division of joint property. To improve fairness and efficiency, it is recommended that Indonesia adopt Malaysia's more structured procedures, while Malaysia can take advantage of the flexibility of Indonesia's mixed legal system. This collaboration is expected to produce a system for the distribution of joint assets that is fairer, more consistent and more responsive to evolving social and economic needs